The Effect of Lidocaine Splash Block Followed by Suspensory Ligament Massage in Female Dogs Undergoing Ovariohysterectomy: A Prospective Study - Eugenia Flouraki; Epameinondas Loukopoulos; Dimitrios Gougoulis; Ioannis Savvas; Chrysoula Margeti; Konstantina Karagianni; Vassiliki Tsioli (Animals)
The administration of lidocaine as part of multimodal analgesia in dogs undergoing ovariohysterectomies demonstrates variable analgesic efficacy. The aim of this prospective, double–blinded clinical study was to evaluate the effectiveness of lidocaine 2% irrigation on the ovarian suspensory ligament, followed by localised massage, in achieving sufficient intraoperative analgesia. Thirty-eight female dogs were randomly divided to two groups and received either a splash block of 0.5 ml lidocaine 2% on each ovarian suspensory ligament (GL) or an equal volume of saline (GNS). All dogs were premedicated with dexmedetomidine (5 μg·kg−1) and buprenorphine (20 μg·kg−1) intramuscularly and meloxicam (0.2 mg·kg−1) subcutaneously. Anaesthesia was induced with propofol and maintained with isoflurane. The surgical procedure was initiated after an adequate depth of anaesthesia was achieved. Heart rate (HR), respiratory rate (fR) and mean arterial pressure (MAP) were continuously monitored. Fentanyl (2 μg·kg−1) was administered as rescue analgesia in case of a 30% increase in HR, fR, or MAP, compared to their values before manipulation of the ovaries. Data were analysed using a mixed model for repeated measures ANOVA and Pearson’s Chi-Square test. The need for rescue analgesia differed significantly between the two groups (p < 0.0005). In GNS, 89.47% (17/19) of the dogs required rescue analgesia, compared to 10.53% (2/19) of the dogs in GL. The relative risk of rescue for the GNS compared to the GL was approximately 8.5. In conclusion, intraoperative analgesia during ovariohysterectomies in dogs can be enhanced using a lidocaine 2% splash block combined with massage of the ovarian suspensory ligament.